2015
DOI: 10.3390/ijerph120911797
|View full text |Cite
|
Sign up to set email alerts
|

Association of TCF7L2 Genetic Polymorphisms with Type 2 Diabetes Mellitus in the Uygur Population of China

Abstract: Background: Genetic polymorphisms of the transcription factor 7-like 2 (TCF7L2) gene have been reported to be strongly associated with type 2 diabetes mellitus (T2DM) in Icelandic, Danish and American populations and further replicated in other European populations, African Americans, Mexican Americans, and Asian populations. The aim of the present study was to investigate the association of TCF7L2 gene polymorphisms with T2DM in a Uygur population of China. Methods: 877 T2DM patients and 871 controls were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…To date, several studies have tested the association between TCF7L2 genetic variations and risk of developing type 2 diabetes mellitus (Assmann et al, 2014;Barros et al, 2014;OuhaibiDjellouli et al, 2014;Guewo-Fokeng et al, 2015;Nanfa et al, 2015;Yang et al, 2015;Yao et al, 2015). Assmann et al (2014), Guewo-Fokeng et al (2015), and Ouhaibi-Djellouli et al (2014) conducted investigations to assess the role of the TCF7L2 rs7903146 polymorphism in the pathogenesis of this disease, reporting that this sequence variant is associated with susceptibility to type 2 diabetes mellitus in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have tested the association between TCF7L2 genetic variations and risk of developing type 2 diabetes mellitus (Assmann et al, 2014;Barros et al, 2014;OuhaibiDjellouli et al, 2014;Guewo-Fokeng et al, 2015;Nanfa et al, 2015;Yang et al, 2015;Yao et al, 2015). Assmann et al (2014), Guewo-Fokeng et al (2015), and Ouhaibi-Djellouli et al (2014) conducted investigations to assess the role of the TCF7L2 rs7903146 polymorphism in the pathogenesis of this disease, reporting that this sequence variant is associated with susceptibility to type 2 diabetes mellitus in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Assmann et al (2014), Guewo-Fokeng et al (2015), and Ouhaibi-Djellouli et al (2014) conducted investigations to assess the role of the TCF7L2 rs7903146 polymorphism in the pathogenesis of this disease, reporting that this sequence variant is associated with susceptibility to type 2 diabetes mellitus in Caucasians. In studies of Chinese populations, Yao et al (2015) and Yang et al (2015) determined that the TCF7L2 rs12255372 polymorphism may also contribute to the risk of developing this condition. However, some investigations have reached inconsistent conclusions (Barros et al, 2014;Pourahmadi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originating from inter-marriage between Caucasians and Mongolians, the Uygur people have their own language, culture, genetic background, lifestyle, and dietary habits. Previous reports showed differences between Uygur and Han regarding the prevalence of T2DM [ 25 ] and genetic polymorphism [ 26 , 27 ]. The current study sought to assess the differences in prevalence of T2DM and metabolic risk factors among general and diabetic populations and their variations across compared populations in Xinjiang, China, drawn from urban and rural Uygur settlements.…”
Section: Introductionmentioning
confidence: 99%
“…TCF7L2 (chr10: 112,950,250‐113,167,678/hg38), transcription factor 7‐like 2, is a component of the Wnt pathway, and variants in this locus have been strongly associated with type 2 diabetes mellitus (T2D) across different world populations and ethnic groups (Grant et al, ; Yao et al, ). Miyake et al () and Ng et al () studied the intronic polymorphism rs11196205 C > G and suggested an association between the ancestral allele C and higher risk of T2D in Hong Kong Chinese and Japanese patients.…”
Section: Methodsmentioning
confidence: 99%